Solution properties, unperturbed dimensions, and chain flexibility of poly(1‐adamantyl acrylate). Issue 20 (11th August 2017) - Lu, Wei; Yin, Panchao; Osa, Masashi; Wang, Weiyu; Kang, Nam‐Goo; Hong, Kunlun; Mays, Jimmy W.
ABSTRACT: Poly(1‐adamantyl acrylate) (PAdA) exhibits much higher glass transition and degradation temperatures than other polyacrylates. However, the quantitative evaluation of the stiffness of this polymer chain has not been reported previously. In this study, the dilute solution properties and conformational characteristics of PAdA were evaluated using viscometry and scattering techniques. The unperturbed dimensions of this polymer were evaluated using the Burchard–Stockmayer–Fixman extrapolation and the touched‐bead wormlike chain model. The PAdA chain has a comparable persistence length, diameter per bead and characteristic ratio to poly(methyl methacrylate) and polystyrene. All these results indicate that PAdA is less flexible than common polyacrylates. In addition, the second virial coefficients ( A 2 ) of PAdA in different solvents obtained by static light scattering were compared. Among the solvents investigated, tetrahydrofuran is a moderate solvent. Radius of gyration of a polymer sample in the various solvents ranged from 16.8 to 30.3 nm. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1526–1531 Abstract : The conformational characteristics and unperturbed dimensions of poly(1‐adamantyl acrylate), obtained from viscometry and scattering techniques, indicates its chain stiffer as compared to common polyacrylates.